2000
DOI: 10.1029/1999ja900430
|View full text |Cite
|
Sign up to set email alerts
|

A four‐fluid turbulence‐driven solar wind model for preferential acceleration and heating of heavy ions

Abstract: Abstract. We present for the first time a one-dimensional, four-fluid turbulencedriven solar wind model in order to investigate the preferential acceleration and heating of heavy ions by the resonant cyclotron interaction with parallel-propagating left-hand-polarized ion cyclotron waves. The model contains four species: electrons, protons, alpha particles, and one species of minor ions. A Kolmogorov type of cascade effect is introduced to transfer energy from the low-frequency Alfv•n waves to the high-frequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
52
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 39 publications
2
52
2
Order By: Relevance
“…The cascade is able to explain the magnetic field spectrum evolution and to account for the proton heating beyond 10 solar radii (Tu 1987(Tu , 1988. In a series of papers, Hu and his coauthors applied this idea to the inner corona, and found that the cascade indeed is able to account for the heating and acceleration of fast solar wind (including minor ions) originating in coronal holes (Hu et al , 2000. In these studies, a hot corona was treated as a boundary condition, the creation of a steep transition region and a hot corona were not considered.…”
Section: Introductionmentioning
confidence: 99%
“…The cascade is able to explain the magnetic field spectrum evolution and to account for the proton heating beyond 10 solar radii (Tu 1987(Tu , 1988. In a series of papers, Hu and his coauthors applied this idea to the inner corona, and found that the cascade indeed is able to account for the heating and acceleration of fast solar wind (including minor ions) originating in coronal holes (Hu et al , 2000. In these studies, a hot corona was treated as a boundary condition, the creation of a steep transition region and a hot corona were not considered.…”
Section: Introductionmentioning
confidence: 99%
“…Some of them include Alfvén waves and/or ion-cyclotron resonance as a dissipation process of the high frequencies waves (e.g., Tu and Marsch, Correspondence to: L. Dolla (dolla@sidc.be) 1997; Hu et al, 2000;Vocks, 2002;Bourouaine et al, 2008b;Landi and Cranmer, 2009;Isenberg and Vasquez, 2009). In this respect, coronal holes are of particular interest as the source of the fast solar wind.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical studies of ion-cyclotron resonance have been developed and applied to the heating of the solar corona and the solar wind (Marsch et al, 1982;Axford and McKenzie, 1992;Tu and Marsch, 1997;Li et al, 1999;Hollweg, 2000;Hu et al, 2000;Cranmer, 2000;Hollweg and Isenberg, 2002). However, there are theoretical difficulties with the application of the ion-cyclotron mechanism for coronal heating, and its role is not yet fully understood (Ofman and Davila, 1997;Cranmer, 2000;Isenberg, 2004).…”
Section: Introductionmentioning
confidence: 99%